THE DURATION OF PERINEAL WOUND HEALING BETWEEN BASTE AND INTERRUPTED SUTURE AMONG POSTPARTUM MOTHERS IN BANTUL, YOGYAKARTA, INDONESIA - Isti Chana Zuliyati; Umu Hani Edi Nawangsih; Dian Pratiwi; Ajeng Hayuning Tiyas (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Suture is a most used technique to heal perineal wound after delivery baby. Midwives often offer baste and disconnected suture for the healing process. Aims: This study aimed to determine the duration of perineum wounds healing between the two suture techniques, baste and disconnected suture. Methods: The study employed a quasi-experimental methods with a longitudinal approach. A total of 24 postpartum mothers who suffered perineum wounds degree II, no smoking, 20-35 years old, no obese, no DM, and no infections, was taken using random sampling. Seven validated parameters in assessing the perineum wound healing process were asked by the researchers during the observation including the status of the stiche, openess, festering, swollen, redness in the skin around the stiches, pain, and smell. The data was then analyzed by independent T-test. Results: The results showed that the average length of the perineum wound healing in a private midwife clinic BPM Umu Hani by baste suturing technique was 7.42 days, and it was significantly shorter (p value = 0.003) than the healing by interrupted suturing technique (9.33 days). Conclusion: Disconnected suturing technique can be a preference for perineal wound healing after delivery baby. However, the midwifery should pay attention to the needs of the postpartum mothers before propose the technique.